Gastroesophageal reflux disease and risk for arrhythmias: a Mendelian randomization analysis - Liang, JunHao; Tang, LuYi; Yang, JinHui; Li, Yi; Yang, XiQiao; Hou, ChiJun (Frontiers in Cardiovascular Medicine, 2024)
Background: Clinical observations and epidemiological studies suggest a potential linkage between gastroesophageal reflux disease (GERD) and arrhythmias, yet the underlying mechanism remains elusive. This study investigates the causal relationship between GERD and four types of arrhythmia through a genetic lens, employing Mendelian randomization analysis to elucidate the directionality of these associations.Methods: Selected single nucleotide polymorphisms (SNPs) from genome-wide association study (GWAS) data were utilized as instrumental variables. The inverse variance weighting (IVW) method, MR-Egger regression analysis, and the weighted median method were employed in two-sample Mendelian randomization analysis. Horizontal pleiotropy was detected and corrected using the MR-PRESSO test and MR-Egger regression. The stability and reliability of the Mendelian randomization results were assessed using the leave-one-out method, Cochran's Q test, and funnel plots. The causal relationship between GERD and four types of arrhythmias was evaluated using the odds ratio (OR).Results: IVW results indicated that GERD could increase the risk of arrhythmias. A one standard deviation increases in the logarithmically transformed GERD score resulted in a 34% increase in the risk of arrhythmia (OR=1.34; 95% CI 1.19-1.51; p=1.66E-06). No significant correlation was found between GERD and other arrhythmias.A causal relationship exists between GERD and arrhythmias, suggesting that GERD increases the risk of developing these arrhythmias.